Sports- and physical activity-related concussion and mental health among adolescents: Findings from the 2017 and 2019 Youth Risk Behavior Survey. (June 2022) - Ziminski, Devon; Szlyk, Hannah S.; Baiden, Philip; Okine, Lucinda; Onyeaka, Henry K.; Muoghalu, Chioma; Cavazos-Rehg, Patricia
Highlights: Nearly 1 in 6 high school students reports a concussion in the past year. Sports and physical activity may be protective factors for mental health problems. Youth concussion increases risk of depression symptoms and suicidal behaviors. Concussion prevention and monitoring are part of youth mental health promotion. Abstract: This study examined the association between self-reported sports- or physical activity-related concussion and symptoms of depression and suicidal behaviors (suicidal ideation, having a suicide plan, and suicide attempts). This study used data from the 2017 and 2019 Youth Risk Behavior Survey (YRBS), a biennial, school-based, nationally representative survey of U.S. students in grade levels 9 to 12 (N = 14, 496). Multivariate logistical regression models assessed the association between self-reported sports-or physical activity-related concussions and suicidal behaviors among students, controlling for a range of demographic and psychosocial variables. Altogether, 13.6% of students reported a sports-or physical activity related concussion in the past 12 months. Among youth, sports-or physical activity related concussions were significantly associated with greater odds of symptoms of depression, suicidal ideation, making a suicide plan, and suicide attempts compared to other youth who did not experience sports- or physical activity-related concussion. Findings highlight increased risk for adverse mental health outcomes among students with sports-or physical activity related concussions. Providing resources for students to engage in physical activity and sports teams may help prevent the onset of depression and suicidal behaviors; however, resources must also be available to monitor any concussions related to these activities to provide support for student emotional well-being.